Nanomaterial-modified electrodes for biosensing - Wan Salim, Wan Wardatul Amani (Society for Research Development, 2020)
Biosensors are analytical devices that transduce biochemical signals into measurable electrical signals. One of the challenges in biosensor development is to transduce signals generated from biorecognition events. Nanomaterials from carbon-based materials such as graphene and its derivatives have been extensively used for improving sensitivity and lowering detection limits of biosensors owing to their ability to increase surface area for biomolecule attachment while improving electron-transfer kinetics at the surface of electrodes. Nanomaterials deposited on electrodes are often in a composite form, where two or more materials are combined and deposited on electrode surfaces. For the past several years, our group has been focusing on understanding the synergistic properties of carbon-based nanomaterials with polymer – both conductive and non-conductive – for enhancing transduction of biorecognition events for applications in non-invasive diabetes monitoring (Abd-Wahab et.al, 2019), water-quality monitoring (Benoudjit et. al., 2018, 2020), and space biology (Park et. al., 2018).